Study on Dynamic Characteristics of Drill String Considering Rock-Breaking Process - Liang, Deyang; Guan, Zhichuan; Xu, Yuqiang; Liu, Yongwang (Frontiers in Earth Science, 2021)
Abstract: Using various tools to obtain downhole data to reach a precise pore pressure model is an important means to predict overpressure. Most downhole tools are connected to the lower end of drill string and move with it. It is necessary to understand the motion state and dynamic characteristics of drill string, which will affect the use of downhole tools. In this paper, a drilling process considering rock-breaking process in vertical wells is simulated using finite element method. In the simulation, gravity is applied to the whole drill string. The contact force between PDC bit and formation is the weight on bit (WOB). And a rotation speed is applied to the upper end of drill string. Analysis of the results shows that the vibration amplitude of bottom hole WOB (contact force between PDC bit and formation, which is the real WOB in drilling process) is bigger than the amplitude of wellhead WOB (acquired through conversion using Hook load, which is on behalf of the WOB obtained on drilling site). Both wellhead WOB and bottom hole WOB decline with a fluctuation in drilling process. In small WOB and low rotation speed conditions, the fluctuation of wellhead WOB focuses on low frequency, the fluctuation of bottom hole WOB focus on high frequency, and the phase of them are not identical. In big WOB and high rotation speed conditions, the fluctuation of wellhead WOB and bottom hole WOB both become more irregular. As for wellhead torque and bottom hole torque, the fluctuation of them mainly focuses on low frequency. And in high rotation speed conditions, wellhead torque may become negative. The research results are beneficial to the usage of downhole tools.